PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING WORDWALL TERHADAP MOTIVASI DAN BERPIKIR KREATIF SISWA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Elvira, Vina; Tobroni; Hadiansah, Dede (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the problem of a less varied learning model that makes students less active and less creative in thinking. This study aims to determine the effect of the Game Based Learning wordwall learning model on the Motivation and creative thinking of elementary school students. This study uses a quantitative research approach with an experimental method and the research design used is the Intact-Group Comparison design in the form of a Pretest-Posttest Control Group design. The population of this study was taken from all fifth grade elementary school students who are located at the UPTD SDN 1 Tugu Kidul in the 2024/2025 academic year. Using a random sampling technique. And based on the results of the research that has been used, namely obtaining the calculation of t-test data (independent sample t-test) the results of student learning motivation t value (6.476) with a sig. (2-tailed) 0.000 which means the sig. <a (0.05), so it can be concluded that there is a significant influence on the use of the Game Based Learning Wordwall learning model on the learning motivation results of fifth grade students at the UPTD SDN 1 Tugu Kidul. And in the data of students' creative thinking results, the value of t = 3.817 was obtained with a sig. (2-tailed) value of 0.000. which means the sig. < a (0.05). So it can be concluded that there is a significant influence on the use of the Game Based Learning Wordwall learning model on the learning outcomes of class V students at UPTD SDN 1 Tugu Kidul.